Solidarity for all : building hope against fear and devastation : 2014-2015 : 4 years of resistance and solidarity (Athens: Solidarity 4 All, 2015)
"DIGITAAL TE RAADPLEGEN IN DE LEESZAALPVDA-solidariteitscongres"